Technical efficiency and productivity of farms: A periurban case study analysis - Anna Gaviglio; Rosalia Filippini; Fabio Albino Madau; Maria Elena Marescotti; Eugenio Demartini (Agricultural and Food Economics, 2021)
Periurban farming systems are characterized by the need to adapt the farming practices coping with a modified natural and social environment. Questions are thus posed on the efficient use of the inputs. The purpose of this study is to estimate the technical efficiency and the productivity of periurban farms. To do so, the study employs a data envelopment analysis that properly captures the heterogeneity of the periurban farming system. The sample considered livestock and crop farms, located in the South Milan Agricultural Park, where 50 farms were selected and interviewed. Results show that crop farms are more efficient than livestock farms, but they have a less productive technology. The participation in short food supply chains and the multifunctional agriculture does not affect the levels of technical efficiency of the farms. Policies are thus needed to improve the education level of farmers and to sustain the efficiency of farms that diversify the farm's economy.
Keywords: 330; Data envelopment analysis; Italy; Periurban farming system